The athlete`s heart - D`Silva, A.; Sharma, S. (Echocardiography, 2018)
Individuals who exercise intensively for more than 4 h per week, develop a constellation of physiological, structural and electrical alterations within the heart which are collectively termed the `athlete`s heart`. The role of these changes is to facilitate rapid filling of the heart and permit the augmentation of stroke volume to generate a large and sustained increase in cardiac output for prolonged periods. On occasion, these physiological adaptations overlap with those observed in the morphologically mild primary cardiomyopathies. The distinction between physiological cardiac enlargement and a cardiomyopathy is crucial considering that the cardiomyopathies account for up to 40% of all sudden cardiac deaths in athletes. An erroneous diagnosis has the potential for very serious consequences; for example, an incorrect diagnosis of athlete`s heart in someone with a cardiomyopathy may jeopardize a young life, whereas an incorrect diagnosis of cardiomyopathy in someone with athlete`s heart may lead to unnecessary disqualification from competitive sport. The aim of this chapter is to provide a methodical approach in the echocardiographic assessment of an athlete with view to differentiation between physiological adaptation and cardiac pathology.